3′phosphoinositide-dependent kinase-1 is essential for ischemic preconditioning of the myocardium - Budas, Grant R. (2006)
Brief periods of ischemia and reperfusion that precede sustained ischemia lead to a reduction in myocardial infarct size. This phenomenon, known as ischemic preconditioning, is mediated by signaling pathway(s) that are yet to be fully defined. 3′-phosphoinositide-dependent kinase-1 (PDK1) has been implicated in numerous cellular processes. However, the involvement of PDK1 in preconditioning has yet to be elucidated. Studying PDK1 is not as straightforward as it is for the majority of kinases, due to the lack of a specific inhibitor of PDK1. Therefore, we have taken advantage of PDK1 hypomorphic mutant mice with reduced expression of PDK1 to study the role of PDK1 in preconditioning. Whole heart and single cell models of preconditioning demonstrated that the hearts and cardiac cells from PDK1 hypomorphic mice could not be preconditioned. The cardioprotective effect of PDK1 was not related to the effect that preconditioning has on sarcolemmal membrane action potential as revealed by di-8-ANEPPS, a sarcolemmal-potential sensitive dye, and laser confocal microscopy. In contrast, experiments with JC-1, a mitochondrial membrane potential-sensitive dye, has demonstrated that intact PDK1 levels were required for preconditioning-mediated regulation of mitochondrial membrane potential. Western blotting combined with functional experiments have shown that intact PDK1 levels were required for preconditioning-induced phosphorylation of protein kinase B (PKB), glycogen synthase kinase-3β (GSK-3β), and cardioprotection. We conclude that PDK1 mediates preconditioning in the heart by regulating activating PKB-GSK-3β to regulate mitochondrial but not sarcolemmal membrane potential. 3′phosphoinositide-dependent kinase-1 (PDK1) is essential for ischemic preconditioning of the myocardium.